Oxford Handbook of Clinical Medicine, 7th Edition - Longmore, Murray, Wilkinson, Ian B; Turmezei, Tom; Cheung, Chee Kay (OXFORD UNIVERSITY PRESS, 2007)
Who needs handbooks? With so many wonderful guidelines emanating from national institutions and Royal Colleges, and so much evidence-based medicine on the web, the idea of a handbook might appear redundant. But just how wonderful are all these guidelines? Let us look at the evidence: in one study of a quiet day on call, 18 patients were seen by one doctor, who made 44 diagnoses. The guidelines advising on these conditions ran to 3679 pages.1 All these guidelines no doubt needed to be read carefully and in full. Carefully! In full!! Just what planet are we on if we expect this to happen? Pluto, it turns out. Each day on Pluto lasts 153.36 hours.2 Allowing 2 minutes a page and a few seconds for reflection, this is just long enough to digest the necessary guidelines. From this we conclude that every junior doctor should be provided with breathing apparatus to survive in the rarefied atmosphere which gives rise to guidelines, as well as a team of readers to give advice as he or she works at the bedside. Pie in the sky? Not quite. Here on Earth, the answer lies in your own hands as you read this, and OUP put it there in the hope and certain knowledge that this bird in your hand is worth at least two on Pluto. We welcome Tom Turmezei and Chee Kay Cheung, who breathe new life into this editionÃ¢â‚¬â€which goes to press 21 years after our first edition. We are aware that by being 21 we may be regarded as being almost established: we would far rather continue to enjoy the fate of our first edition, which was banned from two medical schoolsÃ¢â‚¬â€so far as we could tell for making learning medicine too easy. Or perhaps it was for saying that we should work for our patients, not our consultants. To revive this sense of the subversive we have run comments orthogonal to the text (sometimes literally and sometimes metaphorically)Ã¢â‚¬â€to act as a counter to our more Panglossian sentiments, which might otherwise fatuously indicate that everything is for the best in the best of all possible wards. Voltaire, the creator Panglos, like all true saprophytes (Candida included), fed for ever off decaying matter (the effete French Court)Ã¢â‚¬â€whereas we take our nourishment from the living wells of knowledge embodied in Medline, the BMJ, and the New England Journal of Medicine. This edition embodies countless changesÃ¢â‚¬â€the most obvious being the addition of a Radiology chapterÃ¢â‚¬â€and the introduction of colour images throughout the text. But the main thing we bring to our readers is a friend in the pocketÃ¢â‚¬â€wearing bright new underclothes, and freshly recommitted to the task of being your champion, your mentor, and your fond supportÃ¢â‚¬â€come what may.